Doses de superfosfato simples na produção da berinjela ‘ciça’ em cassilândia (MS) Brasil - Zonta, Tiago Trevelin [UNESP]; Biscaro, Guilherme Augusto; Tosta, Mauro da Silva; Medeiros, Luciana Freitas de; Soratto, Rogério Peres [UNESP]; Tosta, Priscilla de Aquino Freire (My University, 2010)
The objective of this experiment was to evaluate the answer of the eggplant (Solanum melongena L.) submitted to different applied match doses in the planting hole. The treatments were composed by four doses of simple superphosphate (0, 1000, 2000, 3000 kg.ha-1), the experimental design was randomized block, with five repetitions, tends each unit experimental four plants. The phosphorus fertilized soil propitiated increase of the diameter of the lap of the adult plant, of the number of fruits for plant and productivity of fruits; could be used doses among 1814 to 2054 kg ha-1 of simple superphosphate in the conditions of Cassilandia (State of Mato Grosso do Sul - Brazil).

O objetivo deste experimento foi avaliar a resposta da berinjela (Solanum melongena L.) submetida à diferentes doses de fósforo aplicadas na cova de plantio. Os tratamentos foram compostos por quatro doses de superfosfato simples (0, 1000, 2000, 3000 kg ha-1; o experimento foi conduzido no delineamento experimental em blocos casualizados, com cinco repetições, tendo cada unidade experimental quatro plantas. A adubação fosfatada propiciou aumento do diâmetro do colo da planta adulta, do número de frutos por planta e produtividade de frutos; podendo ser utilizada doses entre 1814 a 2054 kg.ha-1 de superfosfato simples nas condições de Cassilândia (MS). Palavras-chave: Adubação fosfatada; características de frutos; Solanum melongena L.
Doses of simple superphosphate in the production of the eggplant 'ciça' in cassilandia (State of Mato Grosso of the Sul – Brazil)
Keywords: Adubação fosfatada; Características do fruto; Solanum melongena